Have Exchange Traded Funds Influenced Commodity Market Volatility? - Shaen Corbet; Cian Twomey (International Journal of Economics and Financial Issues, 2014)
Exchange Traded Funds (ETFs) have existed since the late 1980s, but were first traded on commodity markets in the early 2000s. Their inception has been linked by some market analysts with the large commodity price increases and volatility evident between 2007 and 2009. This research analyses forty-four ETFs across seventeen commodity markets and focuses on the role that the product has played, either as an accelerant for mispricing in international commodity markets, or as a mechanism for liquidity improvements, thereby increasing the speed of the transfer of information. An EGARCH model is used to investigate whether the volatility and liquidity effects are more pronounced in larger or smaller sized commodity markets. The results indicate that larger market-proportional ETF holdings are associated with higher EGARCH volatility. Smaller commodity markets are found to have increased liquidity flows, indicating benefits from ETF investment. The findings in this paper support calls for more intense regulation of the ETF industry and more investigation into the investment practices and rebalancing processes of the funds in question. The need for regulation of investment size and the imposition of market ownership caps cannot be rejected.